2016
DOI: 10.5539/ies.v9n4p257
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Socioeconomic Status on Academic Competence: A Perspective for Teachers

Abstract: Studies suggest that socioeconomic status is a strong predictor of academic achievement. This theoretical paper proposes that despite the fact that low-socioeconomic status represents a risk factor that seems to undermine attentional skills and thus academic achievement, emerging evidence suggests the potential of new approaches, interventions and cognitive training programs to reverse the negative effects of poverty. The evidence presented in this paper may be of particular interest for teachers because it pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
1
11
0
3
Order By: Relevance
“…The study also indicated that associations between implicit theories of intelligence and school achievement are significant for specific categories of students, such as students from disadvantaged families or affected by low parental support. According to previous studies, the socio-economic status may determine high levels of stress, anxiety and self-esteem, thus negatively influencing learning processes and leading to fixed, dysfunctional beliefs on improving intellectual abilities (e.g., Cedeño et al, 2016). On the other hand, students with high socio-economic status tend to report a better awareness of their metacognitive competences and a rather incremental mentality, given their additional chances to access early in their lives reasonable educational resources, read more and enrich their vocabulary, are exposed to stimulating life experiences such as extracurricular activities (e.g., Hackman et al, 2010;Dolean et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The study also indicated that associations between implicit theories of intelligence and school achievement are significant for specific categories of students, such as students from disadvantaged families or affected by low parental support. According to previous studies, the socio-economic status may determine high levels of stress, anxiety and self-esteem, thus negatively influencing learning processes and leading to fixed, dysfunctional beliefs on improving intellectual abilities (e.g., Cedeño et al, 2016). On the other hand, students with high socio-economic status tend to report a better awareness of their metacognitive competences and a rather incremental mentality, given their additional chances to access early in their lives reasonable educational resources, read more and enrich their vocabulary, are exposed to stimulating life experiences such as extracurricular activities (e.g., Hackman et al, 2010;Dolean et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To Ariani and Ghafournia [1], socio-economic factors play a major role in learners' school achievement in that the higher the parents' level of education, occupation and income, the higher the learners' level of school achievement. Cedeño, Martínez-Arias, and Bueno, [21] found a consistent positive relationship between fathers' earnings and their children's scores in secondary schools.…”
Section: Socio-economic Status and Performancementioning
confidence: 77%
“…Individuals are never equal nor do they have equal opportunities to engage in societal activities to get equal rewards. Socio-economic status of a family has been defined as the position of a family in the social class [21]. This could be determined by parents' educational level, occupation and income.…”
Section: Socio-economic Status and Performancementioning
confidence: 99%
“…A nemzetközi szakirodalom a nyelvi hátrány fogalmát összefüggésbe hozza a kognitív képességekkel, a szövegértés kompetenciájával, valamint különösen a figyelemmel és figyelemmegtartással kapcsolatos problémákkal, melyek eredendően a családi háttérhez, a családi otthonhoz, valamint a hátrányos helyzethez kapcsolhatók (Cedeno, Martinez-Arías & Bueno, 2016). Megfigyelhető, hogy a hátrányos helyzettel járó stressz gyakran eredményez zavart a figyelemben, memóriában, tanulási folyamatokban (Neville, Stevens, Pakulak, Bell, Fanning, Klein & Isbell, 2013;Stevens, Lauinger & Neville, 2009).…”
Section: A Családi Háttér Szerepe Az Oktatásbanunclassified